PERBANDINGAN PERTUMBUHAN JAMUR Candida albicans PADA MEDIA ALAMI JAGUNG, SINGKONG DAN UBI JALAR KUNING - Atika Nur Safitri; Muhammad Taufiq Qurrohman (Journal of Indonesian Medical Laboratory and Science, 2022)
The laboratory diagnosis of candidiasis can be done by means of microscopic examination, molecular identification, serological tests and culture systems on specimens. In the method of culture of candidiasis disease is done by isolating the fungus Candida albicans from patient samples on the media. Several previous researchers managed to find a natural medium for the growth of the fungus Candida albicans.This research is experimental using Completely Randomized Design (CRD) with 2 treatment factors. Factor 1 is the type of fungus, namely Candida albicans, factor 2 is the type of natural media, namely media from corn, cassava and yellow sweet potato and PDA media as control. In the observation of 48 hours incubation, the average growth ofcolonies Candida albicans was 4.27 on corn media, 5.87 on cassava media, 5.70 on yellow sweet potato media and 2.48 on PDA media. From the results of the Saphiro-wilk test, it was found that the data were normally distributed (p>0.05). The data from the Levene Test showed that the data were assumed to be the same (p>0.05), and thetest One Way ANOVAfound that (p<0.05) which means that there were differences in the growth of Candida albicans on corn, cassava and yellow sweet potato media.